Demand-Driven Approach Perspective is Used to Evaluate Poverty Alleviation Programs, Strategies, and Governance Challenges in Nigeria. - Ajiteru,S.A.R; Sulaiman T.H; Abalaka, J.N (Green Social: International Journal of Law and Civil Affairs, 2025)
This essay was written to investigate why, in spite of the policies that the Nigerian government has put in place, poverty rates are still high. The main obstacle that every accountable and responsive government must overcome is Regardless matter whether the government is a military dictatorship or a democracy, it must improve and give greater meaning to the lives of its citizens if it is to remain relevant and legitimate in the eyes of the governed. Since independence, every succeeding administration has implemented some kind of plan to lessen the suffering of the populace and make them happy.Prior to and during the Structural Adjustment Program (SAP), it was noted that the majority of these programs were supply-driven, meaning they were unable to address the needs of the impoverished and, as a result, had little impact on reducing poverty. In order to reach the target poor, various programs that were introduced after SAP adopted a demand-driven strategy. The purpose of this study are (i) to critically analyze the several programs, reforms, and policies aimed at reducing poverty that have been implemented by Nigerian governments in succession, as well as the factors that contributed to their success or failure. (ii). expresses profoundly helpful measures that, if properly applied, would help the country escape its current poverty trap and put it on the correct path for sustainable economic development rather than just the steady economic progress it has seen over the years.